Long-term mortality and risk factors for development of end-stage renal disease in critically ill patients with and without chronic kidney disease. Issue 1 (December 2015) - Rimes-Stigare, Claire; Frumento, Paolo; Bottai, Matteo; Mårtensson, Johan; Martling, Claes-Roland; Bell, Max
Abstract Introduction Prevalence of chronic kidney disease (CKD) amongst intensive care unit (ICU) admissions is rising. How mortality and risk of end-stage renal disease (ESRD) differs between those with and without CKD and with acute kidney injury (AKI) is unclear. Determining factors that increase the risk of ESRD is essential to optimise treatment, identify patients requiring nephrological surveillance and for quantification of dialysis provision. Method This cohort study used the Swedish intensive care register 2005–2011 consisting of 130, 134 adult patients. Incomplete cases were excluded (26, 771). Patients were classified (using diagnostic and intervention codes as well as admission creatinine values) into the following groups: ESRD, CKD, AKI, acute-on-chronic disease (AoC) or no renal dysfunction (control). Primary outcome was all-cause mortality. Secondary outcome was ESRD incidence. Results Of 103, 363 patients 4, 192 had pre-existing CKD; 1389 had ESRD; 5273 developed AKI and 998 CKD patients developed AoC. One-year mortality was greatest in AoC patients (54 %) followed by AKI (48.7 %), CKD (47.6 %) and ESRD (40.3 %) (P  < 0.001). Five-year mortality was highest for the CKD and AoC groups (71.3 % and 68.2 %, respectively) followed by AKI (61.8 %) and ESRD (62.9 %) (P  < 0.001). ESRD incidence was greatest in the AoC and CKD groups (adjusted incidence rate ratio (IRR) 259 (95 % confidence interval (CI) 156.9–429.1) and 96.4, (95 % CI 59.7–155.6) respectively) and elevated in AKI patients compared with controls (adjusted IRR 24 (95 % CI 3.9–42.0);P  < 0.001). Risk factors independently associated with ESRD in 1-year survivors were, according to relative risk ratio, AoC (356; 95 % CI 69.9–1811), CKD (267; 95 % CI 55.1–1280), AKI (30; 95 % CI 5.98–154) and presence of elevated admission serum potassium (4.6; 95 % CI 1.30–16.40) (P  < 0.001). Conclusions Pre-ICU renal disease significantly increases risk of death compared with controls. Subjects with AoC disease had extreme risk of developing ESRD. All patients with CKD who survive critical care should receive a nephrology referral. Trial registration Clinical trials registration number:NCT02424747 April 20th 2015.